2019
DOI: 10.1007/s40271-019-00388-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Patient Experience of Hypoparathyroidism Symptoms: Development of the Hypoparathyroidism Patient Experience Scale-Symptom (HPES-Symptom)

Abstract: Background and Objective Hypoparathyroidism is a rare endocrine disorder characterized by absent or inappropriately low levels of circulating parathyroid hormone. Patients with hypoparathyroidism receiving standard-of-care therapy report debilitating physical and cognitive symptoms, which may indicate a reduced health-related quality of life. The purpose of this study was to develop a new disease-specific measure of the signs and symptoms of hypoparathyroidism, the Hypoparathyroidism Patient Experience Scale-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…As with all research, there are study limitations to consider when interpreting findings. These have been noted in a prior publication but should be reiterated here [28]. While efforts were made to recruit a diverse sample of participants, the majority were female and had post-surgical HP, which is similar to the sample compositions in other studies of patients with this condition [5,8,33].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…As with all research, there are study limitations to consider when interpreting findings. These have been noted in a prior publication but should be reiterated here [28]. While efforts were made to recruit a diverse sample of participants, the majority were female and had post-surgical HP, which is similar to the sample compositions in other studies of patients with this condition [5,8,33].…”
Section: Discussionsupporting
confidence: 60%
“…A detailed description of the demographic characteristics of the patient study sample has previously been reported [ 28 ]. To briefly summarize these findings, 42 participants were included in data analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the Hypoparathyroidism Patient Experience Scale-Symptom has been developed as a specific tool for patient-reported outcomes in hypoPT ( 8 ). One hundred per cent of the concept elicitation patient group experienced physical symptoms attributed to hypoPT, such as tingling, numbness and paresthesia (88%), muscle cramps (86%), physical fatigue (83%), cognitive dysfunction (86%), impaired memory (57%), impaired ability to have a conversation (50%), and a lack of concentration/focus (43%).…”
Section: Consequences Of Postsurgical Hypoptmentioning
confidence: 99%